EFFECT OF ADDITION EARTHWORMS FRESH (Lumbricusrubellus) IN FEED ON THE WEIGHT OF EGGS, HAUGH UNIT (HU), AND EGGSHELL THICKNESS OF MOJOSARI DUCK - Desy Tri Intan; Edhy Sudjarwo; Heny Setyo Prayogi (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
The purpose of this research was to investigate and evaluate the effect of the addition of fresh earthworms in the feed to the appearance of duck eggshell, duck egg weight, and Haugh units (HU). The materials of this research were 144 female Mojosari duck 12 month of age. The treatments PO = basal feed; P1 = basal feed added 1% with fresh earthworms; P2=  basal feed added 3% with fresh earthworms; P3 = basal feed added 5% with fresh earthworms. Data were analyzed by Completely Randomized Design (CRD) and if there was significant influent it would be tested by Duncan’s Multiple Range Test (DMRT).The results of this research indicate that duck eggs make a difference Mojosari significant influence (P <0.01) the weight of the egg. The addition of fresh earthworms to Haugh units and shell thickness no significant effect (P> 0.05). The highest egg weight was obtained at P3treatment  was 66,83 ± 1,29c, the Haugh unit values ​​were the highest obtained at P0 treatment was 105,65 ± 2,29 and the highest shell thickness was P3 0,191 ± 0,032. The conclusion of this research was addition the fresh earthworm (Lumbricusrubellus) at the level of 5% give best result on appearance of duck eggshell. Keywords :  Earth worm, egg weight, haugh unit (HU), egg shell thickness.